Effect of Sulfation on Zirconia-Pillared Montmorillonite to the Catalytic Activity in Microwave-Assisted Citronellal Conversion - Is Fatimah; Dwiarso Rubiyanto; Thorikul Huda (International Journal of Chemical Engineering)
Preparation of sulfated zirconia-pillared montmorillonite was carried out in two steps; zirconia pillarization and sulfation to zirconia-pillared montmorillonite. The prepared materials were characterized by using X-ray diffraction (XRD), measurement of the specific surface area, total pore volume and pore size distribution by the N2 adsorption method, scanning electron microscopy-energy dispersive X-ray (SEM-EDX), and surface acidity determination by using pyridine adsorption-FTIR analysis. The activity of the materials as catalysts was evaluated for a microwave-assisted conversion of citronellal. The results showed that the prepared materials had a physicochemical character that promoted high catalytic activity to convert citronellal. From varied Zr content and study of the effect of sulfation on the activity, it was found that Zr content and sulfation increase the surface acidity of the material as shown by the higher total conversion and tendency to produce menthol as a product of the tandem cyclization-hydrogenation mechanism.